Incidental Detection of a Rare Coronary Anomaly During Catheter Ablation for Premature Ventricular Complexes: All in One Coronary Ostium - Şener, Yusuf Ziya; Canpolat, Uğur; Yorgun, Hikmet; Hazırolan, Tuncay; Aytemir, Kudret (Acta Medica, 2021)
Single coronary artery is a rare congenital anomaly associated with sudden cardiac death even though most of the cases are asymptomatic. Cardiac computerized tomography angiography plays an essential role in establishing the diagnosis of single coronary artery and designating the arterial course. Being aware of coronary anomaly is crucial in some cases scheduled for catheter ablation of premature ventricular complex neighboring to coronary arteries to prevent radiofrequency ablation related vascular injury.